Synthesis of thieno[3, 4-c] pyrrole-4, 6-dione-based small molecules for application in organic thin-film transistors. (February 2023) - Cyr, Mélanie; Brixi, Samantha; Ganguly, Anindya; Lessard, Benoît H.; Brusso, Jaclyn L.
Abstract: The synthesis of two alternating donor-acceptor (D-A) small molecules revolving around thieno[3, 4-c]pyrrole-4, 6-dione (TPD) as the main acceptor building block is reported herein. The materials are synthesized using a robust Stille coupling to attach the TPD core with thiophene donors on either of its side, and completed with an aldol condensation under mild conditions for the addition of terminal secondary acceptor building blocks, representing a sought out A 2 -D-A 1 -D-A 2 structure. The two newly synthesized materials are set to be used as organic semiconductors in organic thin-film transistor (OTFT) devices. Comparative optical, computational, and electrochemical studies were carried out on these new materials to investigate their ability to act as potential n -type organic semiconductors. The materials were then incorporated into bottom-gate bottom-contact OTFT devices, and subsequent thin-film engineering studies were done to probe the effects that solvent and post-deposition annealing conditions had on device performance. From these conditions, the rhodanine-derived D-A material exhibited the greatest electron field-effect mobility (0.011 cm 2 V −1 s −1 ), and a threshold voltage of 20.1 V under vacuum. Graphical abstract: Image 1 Highlights: Thieno[3, 4-c] pyrrole-4, 6-dione is a good acceptor that can be exploited to create new small molecule organic semiconductors. Performance of thin-film transistors is dependent on thin-film morphology, which can be modified through many conditions.